2014
DOI: 10.14233/ajchem.2014.17750
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Crystal Structure of Optically Active L- and D-Histidine Norcantharimide

Abstract: Land D-histidine norcantharimide was showed significant PP2A inhibitors effect. They were synthesized through a highly efficient combinatorial approach , to a solution of norcantharidin and L-histidine in 95 % EtOH under temperature affords L-histidine norcantharimide in 97 % yield. L-histidine norcantharimide was characterized by X-ray. This single crystal was orthorhombic with the space group P2(1)2(1)2(1). One unit cell dimensions were a = 10.1553(4) Å, b = 10.4840(5) Å and c = 12.8749(6) Å, respectively. α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Two large clusters ( Figure 1 (2) were obtained from the in situ reduction with NaBH 4 in methanol. [6] Ferromagnetic interactions are dominating within the (defect-)super-tetrahedron motifs, leading to the ground-state spin of S T 5 73/2 for 1 and S T 5 32 for 2. The 2DS M values obtained from VTVF magnetization were 9.0 J kg 21 K 21 and 9.5 J kg 21 K 21 at 7 T for 1 and 2, respectively, which are both close to the calculated values (10.1 J kg 21 K 21 for 1 and 11.3 J kg 21 K 21 for 2) for their ground-state spins.…”
Section: By Increasing Ground-state Spinmentioning
confidence: 99%
See 1 more Smart Citation
“…Two large clusters ( Figure 1 (2) were obtained from the in situ reduction with NaBH 4 in methanol. [6] Ferromagnetic interactions are dominating within the (defect-)super-tetrahedron motifs, leading to the ground-state spin of S T 5 73/2 for 1 and S T 5 32 for 2. The 2DS M values obtained from VTVF magnetization were 9.0 J kg 21 K 21 and 9.5 J kg 21 K 21 at 7 T for 1 and 2, respectively, which are both close to the calculated values (10.1 J kg 21 K 21 for 1 and 11.3 J kg 21 K 21 for 2) for their ground-state spins.…”
Section: By Increasing Ground-state Spinmentioning
confidence: 99%
“…If magnetic anisotropy is introduced into the investigated compound, the 2S11 degenerate ground state is split into doublets or even singlets, giving rise to a decrease in 2DS M compared to Rln(2S11) in the case of Eq. (6). For a Kramers system (half-integer spin) with axial ZFS parameter (D), or a non-Kramers system (integer spin) with negative D, the ground magnetic state is doubly degenerate.…”
Section: By Reducing Magnetic Anisotropymentioning
confidence: 99%
“…Cobalt tungstate is an inexpensive and highly twisted octahedral material, it has been widely concerned as an effective electrocatalyst for water splitting due to its suitable electronic band structure, relatively high electronic conductivity, effective electrochemical and ionic properties [15,20,21] . It was revealed that amorphous CoWO 4 has lower overpotential and Tafel slope than crystalline, whereas the current density of crystalline CoWO 4 was two orders of magnitude higher than those of amorphous [22–25] . The reason is that the two crystalline materials have different reaction mechanisms in water oxidation decomposition.…”
Section: Introductionmentioning
confidence: 99%